2022
DOI: 10.3390/biomedicines10030577
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor Combination Therapy versus Sunitinib as First-Line Treatment for Favorable-IMDC-Risk Advanced Renal Cell Carcinoma Patients: A Meta-Analysis of Randomized Clinical Trials

Abstract: Background: Novel combination therapies have been shown to improve the outcomes of treatment-naive patients with locally advanced or metastatic renal cell carcinoma (aRCC). However, the optimal systemic therapy for aRCC of favorable risk has yet to be clarified. We aimed to evaluate the efficacy and safety of different immunotherapy (IO) combinations, either with another IO (IO–IO) or with an antiangiogenic (IO–TKI), versus sunitinib in the first-line setting in aRCC patients with favorable IMDC risk. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…4 Recent studies have shown that IO + IO combination therapy improves the prognosis for patients with mRCC 19,27 ; however, a meta-analysis of randomized clinical trials showed no significant difference in OS in patients with favorable IMDC risk for IO + TKI combination therapy compared with TKI monotherapy with sunitinib. 28 When this study began, TKI monotherapy was the standard therapy. Thus, patients treated with nivolumab as second-line in this study received IO therapy after TKI monotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recent studies have shown that IO + IO combination therapy improves the prognosis for patients with mRCC 19,27 ; however, a meta-analysis of randomized clinical trials showed no significant difference in OS in patients with favorable IMDC risk for IO + TKI combination therapy compared with TKI monotherapy with sunitinib. 28 When this study began, TKI monotherapy was the standard therapy. Thus, patients treated with nivolumab as second-line in this study received IO therapy after TKI monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…According to National Comprehensive Cancer Network guidelines, IO + TKI or TKI monotherapy is the first‐line treatment recommended for patients with favorable IMDC risk 4 . Recent studies have shown that IO + IO combination therapy improves the prognosis for patients with mRCC 19,27 ; however, a meta‐analysis of randomized clinical trials showed no significant difference in OS in patients with favorable IMDC risk for IO + TKI combination therapy compared with TKI monotherapy with sunitinib 28 . When this study began, TKI monotherapy was the standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with localized RCC receiving treatments like radiofrequency ablation, enucleoresection or simple nephrectomy have improved disease-free survival rates up to 90% [4,5], while the treatment methods for advanced and metastatic ccRCC are still limited. Immunotherapy is currently used as a first-line treatment [6], but only a small proportion of patients can benefit from immunotherapy due to the complexity and highly modulated nature of the immune system [7].…”
Section: P R E P R I N Tmentioning
confidence: 99%
“…The current STAR trial also demonstrated that planned breaks in tyrosine kinase inhibitor treatment in patients with renal cell carcinoma might be a reasonable option when there is a patient or healthcare need (e.g., a pandemic or drug shortage); with caution, this should be exercised since these patients would typically have shorter progression-free survival than those receiving first-line tyrosine kinase inhibitors [9]. In addition, a meta-analysis showed that favorable-risk group patients who have been treated with TKI (sunitinib) have similar overall survival rates compared to immunotherapy plus TKI treatment regimens [10]. On the other hand, the IMDC and Memorial Sloan Kettering Cancer Center models stratify patients with 1 or 2 risk factors as intermediate prognoses.…”
Section: Introductionmentioning
confidence: 99%